Polyamide resin composition and molded article
By combining ethylene-butene copolymer and copper compound in the polyamide resin and using an appropriate amount of black colorant, the problem of color instability of the polyamide resin composition in a thermal environment is solved, and color stability and impact resistance are achieved Improvement of properties and heat resistance.
Patent Information
- Application Number
- CN202410806373.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-22
- Filing Date
- 2024-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
The use of black colorants in existing polyamide resin compositions under long-term exposure to thermal environments causes the color to gradually fade, lose its original black, and fail to maintain the color stability before thermal aging.
Using a polyamide resin composition containing an ethylene-butene copolymer and a copper compound, and adding an appropriate amount of black colorant therein to ensure compatibility and reactivity of the colorant with the polyamide resin, grafting ethylene by maleic anhydride -The combination of butene copolymer and copper compound forms stable color characteristics.
It realizes the stability of black color under high temperature environments, while improving the impact resistance and heat aging resistance of the material, avoiding color discoloration problems.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a polyamide resin composition and a molded product. Background Art
[0002] Polyamide resins are used in various industrial fields due to their good fluidity, high heat resistance, and mechanical properties. In recent years, so-called polymer alloys have been proposed, which are obtained by blending and compounding various elastomers with polyamide in order to further improve the impact resistance that cannot be obtained with a single polyamide resin.
[0003] However, these elastomers are generally nonpolar polymers and are generally incompatible with polyamides. Therefore, so-called modified elastomers are used, which are obtained by adding a functional group reactive with polyamides, such as α·β unsaturated carboxylic acid such as maleic anhydride or its derivatives, to the elastomer.
[0004] As a specific measure for improving impact resistance, a technique using a modified ethylene-butene copolymer is common, as described in Patent Document 1. Patent Document 1 discloses that the compatibility of an ethylene-butene copolymer with polyamide is dramatically improved, thereby significantly improving the impact resistance of the polyamide.
[0005] In general, when polyamide is required to have glossiness and is used for outdoor applications, it is often used as a molded article colored black with a black colorant such as carbon black or aniline black compound in order to improve weather resistance.
[0006] Furthermore, as a technique for improving the heat aging resistance of a polyamide resin, a technique of adding a copper compound (copper oxide or salt) to the polyamide resin is generally known.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-69190 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Although the impact resistance is improved by the polymer alloy of polyamide and ethylene-butene copolymer, and the heat aging resistance is improved by adding a copper compound, there is a problem that the molded article including the polyamide resin composition to which a black colorant such as carbon black or aniline black compound is added for black coloring has the following problem: the black color gradually fades due to long-term exposure to a heat environment and eventually changes to brown.
[0012] Based on the above situation, a black polyamide resin composition is required which has excellent color stability and does not change color due to heat aging treatment even if black coloring is performed using a black colorant, while improving the impact resistance and heat aging resistance of polyamide by using an ethylene-butene copolymer and a copper compound.
[0013] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a black colored polyamide resin composition having both impact resistance and heat aging resistance and excellent color stability before and after heat aging even when colored with a black colorant, and a molded article using the polyamide resin composition.
[0014] Means used to solve problems
[0015] That is, the present invention is as follows.
[0016] [1] A polyamide resin composition, wherein, relative to 100 parts by mass of a polyamide resin (A), the polyamide resin composition comprises:
[0017] 1.0 to 30.0 parts by mass of an ethylene-butene copolymer (B),
[0018] 0.01 to 1.0 parts by mass of a black colorant (C), and
[0019] Copper compounds (D),
[0020] The ethylene-butene copolymer (B) includes a functional group reactive with the polyamide resin (A), and the mass ratio of the functional group is 0.6 mass % or more and 3.5 mass % or less relative to 100 mass % of the ethylene-butene copolymer.
[0021] The mass ratio of the copper compound (D) is 0.001 to 0.5 parts by mass in terms of copper element content relative to 100 parts by mass of the polyamide resin (A).
[0022] [2] The polyamide resin composition according to [1], wherein the ethylene-butene copolymer (B) is a maleic anhydride grafted ethylene-butene copolymer.
[0023] [3] The polyamide resin composition according to [1] or [2], wherein the black colorant (C) is at least one selected from the group consisting of carbon black and aniline black compounds.
[0024] [4] The polyamide resin composition according to any one of [1] to [3], wherein the polyamide resin (A) is one or more selected from the group consisting of polyamide 66, polyamide 66 / 6I, polyamide 610, polyamide 612, polyamide 6I and polyamide 6.
[0025] [5] A molded article, wherein the molded article is a molded article of the polyamide resin composition according to any one of [1] to [4], and the molded article is used for applications exposed to a heat environment of 100° C. or higher.
[0026] [6] The molded article according to [5], wherein the molded article is a strapping tape or a protector for an automobile.
[0027] Effects of the Invention
[0028] According to the present invention, a polyamide resin composition having both impact resistance and heat aging resistance and excellent color stability, and a molded article using the polyamide resin composition can be provided. DETAILED DESCRIPTION
[0029] Hereinafter, a mode for implementing the present invention (hereinafter referred to as "this embodiment") is described in detail. The following this embodiment is an example for explaining the present invention and is not intended to limit the present invention to the following content. The present invention can be implemented by appropriately modifying it within the scope of its purpose.
[0030] In addition, in this specification, "polyamide" refers to a polymer having an amide (-NHCO-) group in the main chain.
[0031] <Polyamide resin composition>
[0032] The polyamide resin composition of the present embodiment contains a polyamide resin (A), an ethylene-butene copolymer (B), a black colorant (C), and a copper compound (D). The polyamide resin composition of the present embodiment may be a composition containing only the polyamide resin (A), the ethylene-butene copolymer (B), the black colorant (C), and the copper compound (D), or may further contain a fibrous reinforcing material (E) and / or other additives (F).
[0033] 《Polyamide resin (A)》
[0034] Examples of the polyamide resin (A) include, but are not limited to, polyamide resins obtained by polycondensation of diamine and dicarboxylic acid, polyamide resins obtained by ring-opening polymerization of lactam, polyamide resins obtained by self-condensation of aminocarboxylic acid, and copolymers obtained by copolymerization of two or more monomers constituting these polyamide resins. These polyamide resins (A) may be used alone or in combination of two or more.
[0035] The polymerizable monomers serving as raw materials of the polyamide resin (A) will be described in detail below.
[0036] (Diamine)
[0037] Examples of the diamine include, but are not limited to, aliphatic diamines, alicyclic diamines, and aromatic diamines.
[0038] The aliphatic diamine may be a linear saturated aliphatic diamine or a branched saturated aliphatic diamine. Examples of the branched saturated aliphatic diamine include diamines having a substituent branching from a main chain.
[0039] The linear saturated aliphatic diamine preferably has 2 to 20 carbon atoms, and examples thereof include ethylenediamine, propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, and tridecamethylenediamine.
[0040] The branched saturated aliphatic diamine preferably has 3 to 20 carbon atoms, and examples thereof include 2-methylpentamethylenediamine (also referred to as "2-methyl-1,5-diaminopentane"), 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 2-methyloctamethylenediamine, and 2,4-dimethyloctamethylenediamine.
[0041] Examples of the alicyclic diamine (also referred to as alicyclic diamine) include 1,4-cyclohexanediamine, 1,3-cyclohexanediamine, and 1,3-cyclopentanediamine, but are not limited thereto.
[0042] Examples of the aromatic diamine include, but are not limited to, m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, and p-phenylenediamine.
[0043] These diamines may be used alone or in combination of two or more.
[0044] (Dicarboxylic Acid)
[0045] Examples of the dicarboxylic acid include, but are not limited to, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and aromatic dicarboxylic acids.
[0046] The aliphatic dicarboxylic acid may be a linear saturated aliphatic dicarboxylic acid or a branched saturated aliphatic dicarboxylic acid, and preferably an aliphatic dicarboxylic acid having a carbon number of 3 or more and 20 or less. Examples of such aliphatic dicarboxylic acids include malonic acid, dimethylmalonic acid, succinic acid, 2,2-dimethylsuccinic acid, 2,3-dimethylglutaric acid, 2,2-diethylsuccinic acid, 2,3-diethylglutaric acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid, and diglycolic acid, but are not limited thereto.
[0047] The number of carbon atoms in the alicyclic structure of the alicyclic dicarboxylic acid (also referred to as alicyclic dicarboxylic acid) is not particularly limited, but is preferably 3 or more and 10 or less from the viewpoint of the balance between water absorption and crystallinity of the obtained polyamide resin (A) component.
[0048] The alicyclic dicarboxylic acid may be unsubstituted or may have a substituent. As the substituent, an alkyl group having 1 to 4 carbon atoms is preferred. As the substituent, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, etc. may be mentioned, but it is not limited thereto.
[0049] Examples of such alicyclic dicarboxylic acids include 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,3-cyclopentanedicarboxylic acid, but are not limited thereto.
[0050] Examples of aromatic dicarboxylic acids include, but are not limited to, unsubstituted or substituted aromatic dicarboxylic acids having 8 to 20 carbon atoms. Examples of substituents include, but are not limited to, alkyl groups having 1 to 6 carbon atoms, aryl groups having 6 to 12 carbon atoms, aralkyl groups having 7 to 20 carbon atoms, halogen groups, alkylsilyl groups having 3 to 10 carbon atoms, sulfonic acid groups, and groups having sulfonates. Examples of halogen groups include, but are not limited to, chloro groups and bromo groups. Examples of salts constituting groups having sulfonates include, but are not limited to, sodium salts.
[0051] Examples of such aromatic dicarboxylic acids include, but are not limited to, terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, and 5-sodium sulfoisophthalate.
[0052] These dicarboxylic acids may be used alone or in combination of two or more.
[0053] (Lactam)
[0054] Examples of lactams include, butyrolactam, pivalolactam, ε-caprolactam, capryllactam, enantholactam, undecanolactam, and laurolactam (lauryllactam), but are not limited thereto. Among them, ε-caprolactam, undecanolactam, or lauryllactam (lauryllactam) is preferred from the viewpoint of polymerization production.
[0055] These lactams may be used alone or in combination of two or more.
[0056] (Aminocarboxylic acid)
[0057] Examples of the aminocarboxylic acid include compounds obtained by ring-opening the above-mentioned lactams, and more specifically, include ω-aminocarboxylic acid and α,ω-aminocarboxylic acid, but are not limited thereto.
[0058] The aminocarboxylic acid may be an aliphatic aminocarboxylic acid or an aromatic aminocarboxylic acid. Examples of the aromatic aminocarboxylic acid include, but are not limited to, p-aminomethylbenzoic acid.
[0059] As the aminocarboxylic acid, from the viewpoint of improving crystallinity, a linear or branched saturated aliphatic aminocarboxylic acid having 4 to 14 carbon atoms substituted with an amino group at the ω position is preferred. Specific preferred aminocarboxylic acids include, but are not limited to, 6-aminocaproic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid.
[0060] These aminocarboxylic acids may be used alone or in combination of two or more.
[0061] Examples of the polyamide resin (A) include polyamide 4 (poly α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecanamide), polyamide 12 (polydodecamide), polyamide 46 (polybutylene adipamide), polyamide 56 (polypentamethylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610 (polyhexamethylene sebacamide), polyamide 612 (polyhexamethylene dodecane diamide), polyamide 116 (polyundecanediamide), polyamide 6I (polyhexamethylene isophthalamide), polyamide PACM12 (polyhexamethylene adipamide), and polyamide 10 (polyhexamethylene sebacamide). dodecanedioylbis(4-aminocyclohexyl)methane), polyamide dimethyl PACM12 (polydodecanediamidebis(3-methyl-4-aminocyclohexyl)methane), polyamide MXD6 (polymethylene adipamide), polyamide 6 / 66 (caprolactam / polyhexamethylene adipamide copolymer), polyamide 66 / 6I (polyhexamethylene adipamide / polyhexamethylene isophthalamide copolymer), polyamide 6I / 6T (polyhexamethylene isophthalamide / polyhexamethylene terephthalamide copolymer), polyamide 6 / 11 (caprolactam / aminoundecanoic acid copolymer), polyamide 6 / 12 (caprolactam / laurolactam copolymer), polyamide 6 / 66 / 12 (caprolactam / polyhexamethylene adipamide / laurolactam copolymer), polyamide TMHT (trimethylhexamethylene terephthalamide), polyamide 4T (polybutylene terephthalamide), polyamide 6T (polyhexamethylene terephthalamide), polyamide 2Me-5T (poly 2-methylpentamethylene terephthalamide), polyamide 9T (polynonane terephthalamide), polyamide 2Me-8T (poly 2-methyloctanediamine terephthalamide), polyamide 6C (polycyclohexane dicarboxamide), polyamide Amine 2Me-5C (polycyclohexanedicarboxylic acid 2-methylpentanediamine), polyamide 9C (polycyclohexanedicarboxylic acid nonanediamine), polyamide 2Me-8C (polycyclohexanedicarboxylic acid 2-methyloctanediamine), polyamide 10T (polydecane terephthalamide), polyamide 11T (polyundecanediamine terephthalamide), polyamide 12T (polydodecane terephthalamide), polyamide 10C (polydecane cyclohexanedicarboxylic acid), polyamide 11C (polyundecanediamine cyclohexanedicarboxylic acid), polyamide 12C (polydodecane cyclohexanedicarboxylic acid), etc., but are not limited to these.
[0062] Among them, the polyamide resin (A) is preferably at least one selected from the group consisting of polyamide 66, polyamide 66 / 6I, polyamide 610, polyamide 612, polyamide 6I, and polyamide 6.
[0063] In addition, as the polyamide resin (A), polyamide 66 or a mixture of PA66 and PA6 is particularly preferred from the viewpoint of improving mechanical strength and fluidity.
[0064] The polyamide resin (A) generally has an amino group or a carboxyl group at the terminal group.
[0065] The ratio of the amount of amino terminal groups in the polyamide resin (A) to the total molar amount of the amount of amino terminal groups and the amount of carboxyl terminal groups [amount of amino terminal groups / (amount of amino terminal groups+amount of carboxyl terminal groups)] is preferably 0.1 or more and less than 1.0, more preferably 0.15 or more and 0.6 or less, and further preferably 0.25 or more and 0.5 or less. When the ratio of the amount of terminal groups is within the above range, there is a tendency that the mechanical strength of the molded article obtained from the polyamide resin composition is more excellent.
[0066] The amino terminal group content of the polyamide resin (A) is preferably 10 μmol / g or more and 100 μmol / g or less, more preferably 10 μmol / g or more and 70 μmol / g or less, and further preferably 15 μmol / g or more and 50 μmol / g or less. When the amino terminal group content is within the above range, the ethylene-butene copolymer (B) tends to be well dispersed in the polyamide resin (A), and the impact resistance tends to be excellent.
[0067] There are no particular restrictions on the method for adjusting the concentration of the terminal groups of the polyamide resin (A), and examples thereof include: a method using a terminal regulator. As a specific example, there can be mentioned: adding one or more terminal regulators selected from the group consisting of monoamine compounds, diamine compounds, monocarboxylic acid compounds, and dicarboxylic acid compounds in a ratio that achieves a predetermined terminal concentration during the polymerization of the polyamide. There are no particular restrictions on the time of adding the terminal regulator to the solvent as long as it performs its original function as the terminal regulator, and for example, it can be when the raw materials of the above-mentioned polyamide are added to the solvent.
[0068] The monoamine compound is not particularly limited, and examples thereof include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine. Among them, butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, or aniline is preferred from the viewpoints of reactivity, boiling point, stability of the end capping, price, and the like. These monoamine compounds may be used alone or in combination of two or more.
[0069] The diamine compound is not particularly limited, and examples thereof include: linear aliphatic diamines such as hexamethylenediamine and pentamethylenediamine; branched aliphatic diamines such as 2-methylpentanediamine and 2-ethylhexamethylenediamine; aromatic diamines such as p-phenylenediamine and m-phenylenediamine; alicyclic diamines such as cyclohexanediamine, cyclopentanediamine and cyclooctanediamine, etc. These diamine compounds may be used alone or in combination of two or more.
[0070] The monocarboxylic acid compound is not particularly limited, and examples thereof include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, methylbenzoic acid, α-naphthoic acid, β-naphthoic acid, methylnaphthoic acid, and phenylacetic acid, etc. These monocarboxylic acid compounds may be used alone or in combination of two or more.
[0071] The dicarboxylic acid compound is not particularly limited, and examples thereof include aliphatic dicarboxylic acids such as malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, 3,3-diethylsuccinic acid, azelaic acid, sebacic acid, and suberic acid; alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; aromatic dicarboxylic acids such as isophthalic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,4-phenylenedioxydiacetic acid, 1,3-phenylenedioxydiacetic acid, biphenylcarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and 4,4'-biphenyl dicarboxylic acid, etc. These dicarboxylic acid compounds may be used alone or in combination of two or more.
[0072] The viscosity of the polyamide resin (A) is not particularly limited, but the formic acid relative viscosity RV is preferably 25 to 50, more preferably 28 to 45, and further preferably 31 to 39 from the viewpoint of achieving a better balance between fluidity and mechanical properties.
[0073] The mass ratio of the polyamide resin (A) relative to 100 mass % of the polyamide resin composition of the present embodiment is preferably 80 mass % or more, more preferably 85 mass % to 99 mass %, further preferably 88 mass % to 98 mass %.
[0074] 《Ethylene-butene copolymer (B)》
[0075] The ethylene-butene copolymer (B) contains a functional group reactive with the polyamide resin (A). The ethylene-butene copolymer (B) can contain a functional group reactive with the polyamide resin (A) by, for example, being modified with a compound containing a polar group, for example, one or more selected from the group consisting of carboxylic acids and derivatives thereof, and unsaturated carboxylic acids and derivatives thereof.
[0076] Examples of the functional group reactive with the polyamide resin (A) include a carboxyl group, an acid anhydride group, a carboxylate group, a carboxylic acid metal salt, a carboxylic acid imide group, a carboxylic acid amide group, and an epoxy group.
[0077] Examples of compounds containing these functional groups include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, mesaconic acid, citraconic acid, glutaconic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, endo-bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic acid, and metal salts of these carboxylic acids; monomethyl maleate, monomethyl itaconate, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, methyl methacrylate, 2-methacrylate. Ethylhexyl ester, hydroxyethyl methacrylate, aminoethyl methacrylate, dimethyl maleate, dimethyl itaconate, maleic anhydride, itaconic anhydride, citraconic anhydride, endo-bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic anhydride, maleimide, N-ethylmaleimide, N-butylmaleimide, N-phenylmaleimide, acrylamide, methacrylamide, glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, glycidyl itaconate, glycidyl citraconic acid, etc. These compounds may be used alone or in combination of two or more. Among them, maleic anhydride is preferably used, and the ethylene-butene copolymer (B) is preferably a maleic anhydride-grafted ethylene-butene copolymer.
[0078] Examples of methods for introducing these functional groups into ethylene-butene copolymers include: (i) a method of copolymerizing a copolymerizable monomer having a functional group during polymerization of the ethylene-butene copolymer; (ii) a method of introducing a functional group into the molecular chain or molecular terminal of the ethylene-butene copolymer using a polymerization initiator, a chain transfer agent, etc.; (iii) a method of grafting a compound having a functional group and a functional group capable of being grafted (grafted compound) onto the ethylene-butene copolymer, etc. These introduction methods can be used alone or in appropriate combination.
[0079] The mass ratio of the functional group that reacts with the polyamide resin (A) is 0.6% to 3.5% by mass, preferably 0.7% to 3.0% by mass, and more preferably 0.8% to 2.5% by mass, relative to 100% by mass of the ethylene-butene copolymer (B). When the mass ratio of the functional group (e.g., anhydride group) is within the above range, impact resistance, fluidity, and discoloration after aging become good.
[0080] The mass ratio of the ethylene-butene copolymer (B) is 1.0 mass parts or more and 30.0 mass parts or less relative to 100 mass parts of the polyamide resin (A). The lower limit of the mass ratio can be 1.2 mass parts, 1.5 mass parts, 1.8 mass parts, 2.0 mass parts, and 2.5 mass parts, respectively, and the upper limit of the mass ratio can be 25.0 mass parts, 20.0 mass parts, 15.0 mass parts, 14.0 mass parts, and 12.0 mass parts, respectively. When the ethylene-butene copolymer (B) is within the above range, there is a tendency that heat aging resistance, impact resistance, and fluidity become good.
[0081] The melt mass flow rate (MFR) of the ethylene-butene copolymer (B) measured under the conditions of a temperature of 190° C. and a load of 2.16 kg according to ASTM D 1238 is preferably 0.1 (g / 10 min) or more and 30 (g / 10 min) or less, more preferably 0.2 (g / 10 min) or more and 20 (g / 10 min) or less, and still more preferably 0.3 (g / 10 min) or more and 10 (g / 10 min) or less. When the melt mass flow rate (MFR) of the ethylene-butene copolymer (B) is within the above range, impact resistance and fluidity become good.
[0082] 《Black Colorant (C)》
[0083] The black colorant (C) is not particularly limited, and examples thereof include aniline black compounds and carbon black.
[0084] As the nigrosine compound, a black azine condensation mixture described in the Color Index as CI Solvent Black 5 and CI Solvent Black 7 can be used. The nigrosine compound can be synthesized, for example, by subjecting aniline, aniline hydrochloride, and nitrobenzene to oxidation and dehydration condensation in the presence of ferric chloride at a reaction temperature of 160° C. to 180° C.
[0085] Nigrosine compounds were generated as a mixture of various compounds, presumably various triphenazines. It is a mixture of azine compounds such as phenazine and phenazine azine.
[0086] Examples of the carbon black include furnace black obtained by a furnace process, channel black obtained by a channel process, acetylene black obtained by an acetylene process, thermal black obtained by a thermal process, and lamp black.
[0087] The average primary particle size of carbon black is preferably 10 nm or more and 40 nm or less, more preferably 10 nm or more and 30 nm or less, and particularly preferably 10 nm or more and 20 nm or less. When the average primary particle size of carbon black is above the lower limit, the dispersibility in the composition can be improved. On the other hand, when the average primary particle size of carbon black is below the upper limit, the softness and elongation of the molded article can be improved.
[0088] Here, the average primary particle size refers to the average value obtained by measuring the particle sizes of 3,000 particles per constituent particle from an aggregate magnified image obtained by the procedure described in ASTM D3849 (Standard Test Methods for Carbon Black - Morphological Characterization by Electron Microscopy) and calculating the average value.
[0089] In addition, it is preferable to use a material with a specific surface area of 50 m2 as measured by the BET adsorption method. 2 / g and above and 300m 2 / g or less, and carbon black having an oil absorption of dibutyl phthalate in the range of 50 mL / 100 g or more and 150 mL / 100 g or less.
[0090] The mass ratio of the black colorant (C) relative to 100 parts by mass of the polyamide resin (A) is 0.01 parts by mass or more and 1.0 parts by mass or less, preferably 0.05 parts by mass or more and 1.0 parts by mass or less, and more preferably 0.08 parts by mass or more and 0.5 parts by mass or less. When the mass ratio of the black colorant (C) is above the above lower limit, a sufficient coloring effect can be obtained. On the other hand, when the mass ratio of the black colorant (C) is below the above upper limit, the softness, tensile elongation and heat aging resistance of the molded product are excellent.
[0091] The black colorant (C) may be prepared as a masterbatch and / or tablet using a polymer as a carrier to form particles. The use of the masterbatch or tablet form improves dispersibility and provides excellent coloring effect and tensile elongation.
[0092] 《Copper Compounds (D)》
[0093] The copper compound (D) is not particularly limited, but is preferably one or more selected from the group consisting of cuprous iodide, cuprous bromide, cupric bromide, cuprous chloride and cupric acetate, and more preferably cuprous iodide or cupric acetate. When the above more preferred copper compounds are used, a polyamide resin composition having better heat aging resistance and capable of more effectively suppressing metal corrosion of the screw and barrel during processing can be obtained.
[0094] From the viewpoint of improving the heat aging resistance of the polyamide resin composition, the mass ratio of the copper compound (D) is 0.001 mass part or more and 0.5 mass part or less, preferably 0.0015 mass part or more and 0.1 mass part or less, and more preferably 0.002 mass part or more and 0.05 mass part or less, in terms of copper element content, relative to 100 mass parts of the polyamide resin.
[0095] Alkali metal halides and alkaline earth metal halides can be used together with the copper compound (D). Examples include, but are not limited to, potassium iodide, potassium bromide, potassium chloride, sodium iodide, sodium bromide, sodium chloride, and mixtures thereof. Among them, potassium iodide, potassium bromide, sodium iodide, and sodium bromide are preferred from the viewpoint of improving heat aging resistance and inhibiting metal corrosion.
[0096] 《Fiber-reinforced materials (E)》
[0097] Examples of the fibrous reinforcing material (E) include glass fibers, carbon fibers, calcium silicate fibers, potassium titanate fibers, aluminum borate fibers, aramid fibers, and cellulose nanofibers.
[0098] Among them, from the viewpoint of increasing the strength and rigidity of the obtained molded product, glass fibers, carbon fibers or potassium titanate fibers having circular or non-circular cross sections are preferred. In addition, glass fibers or carbon fibers having circular or non-circular cross sections are more preferred.
[0099] These fibrous reinforcing materials may be used alone or in combination of two or more.
[0100] As for the glass fiber and the carbon fiber, from the viewpoint of being able to impart excellent mechanical properties to the polyamide resin composition, the number average fiber diameter is preferably 3 μm or more and 30 μm or less, the weight average fiber length is preferably 100 μm or more and 750 μm or less, and the aspect ratio of the weight average fiber length to the number average fiber diameter (the value obtained by dividing the weight average fiber length by the number average fiber diameter) is preferably 10 or more and 100 or less. Among them, it is preferred that the number average fiber diameter is within the above range, the weight average fiber length is within the above range, and the aspect ratio of the weight average fiber length to the number average fiber diameter is within the above range.
[0101] As calcium silicate fibers, from the viewpoint of being able to impart excellent mechanical properties to the polyamide resin composition, the number average fiber diameter is preferably 3 μm or more and 30 μm or less, the weight average fiber length is preferably 10 μm or more and 500 μm or less, and the aspect ratio is preferably 3 or more and 100 or less. Among them, it is preferred that the number average fiber diameter is within the above range, the weight average fiber length is within the above range, and the aspect ratio is within the above range.
[0102] Here, the number average fiber diameter and the weight average fiber length in this specification can be obtained by the following method.
[0103] (Method for determining number average fiber diameter and weight average fiber length)
[0104] The polyamide resin composition is placed in an electric furnace to incinerate the organic matter contained therein. From the obtained residue components, for example, 100 or more fibrous reinforcing materials (E) are randomly selected, observed using a SEM, and their fiber diameters are measured. The average value is calculated from the obtained measured values, thereby being able to determine the number average fiber diameter.
[0105] In addition, the fiber length can be measured using a SEM photograph with a magnification of 1000 times, and the fiber length can be calculated using a predetermined calculation formula (when the fiber lengths of n fibers are measured, weight-average fiber length = Σ (I = 1 → n) (fiber length of the nth fiber) 2 / Σ(I=1→n)(fiber length of the nth fiber)) to find the weight-average fiber length.
[0106] (Silane coupling agent)
[0107] The fibrous reinforcing material (E) may be surface-treated with a silane coupling agent or the like.
[0108] Examples of the silane coupling agent include aminosilanes, mercaptosilanes, epoxysilanes, and vinylsilanes.
[0109] Examples of the aminosilanes include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane.
[0110] Examples of the mercaptosilanes include γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.
[0111] Among them, as the silane coupling agent, aminosilanes are preferred from the viewpoint of affinity with the resin.
[0112] These silane coupling agents may be used alone or in combination of two or more.
[0113] (Shock Agent)
[0114] When glass fibers are used as the fibrous reinforcing material (E), the glass fibers preferably contain a sizing agent. The sizing agent is a component applied to the surface of the glass fibers.
[0115] Examples of the sizing agent include copolymers containing unsaturated vinyl monomers containing carboxylic anhydride and unsaturated vinyl monomers other than the above-mentioned unsaturated vinyl monomers containing carboxylic anhydride as structural units, epoxy compounds, polycarbodiimide compounds, polyurethane resins, homopolymers of acrylic acid, copolymers of acrylic acid and other copolymerizable monomers, and salts of these with primary amines, secondary amines and tertiary amines.
[0116] These sizing agents may be used alone or in combination of two or more.
[0117] (content)
[0118] In the polyamide resin composition of the present embodiment, the content of the fibrous reinforcing material (E) is preferably 0 parts by mass or more and 70 parts by mass or less, more preferably 5 parts by mass or more and 60 parts by mass or less, and further preferably 10 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass of the polyamide resin (A).
[0119] When the content of the fibrous reinforcing material (E) is within the above range, the mechanical strength of the polyamide resin composition and the fluidity during injection molding tend to be more excellent.
[0120] 《Other additives (F)》
[0121] The polyamide resin composition of the present embodiment may contain, in addition to the above components (A) to (E), other additives (F) other than the above components (A) to (E) as necessary within a range that does not impair the effects of the present embodiment.
[0122] Examples of other additives include fillers, heat stabilizers, ultraviolet absorbers, light degradation inhibitors, plasticizers, lubricants, mold release agents, nucleating agents, flame retardants, and other thermoplastic resins, but are not limited thereto.
[0123] Although not particularly limited, when a heat stabilizer, an ultraviolet absorber, an anti-photodegradation agent, a plasticizer, a lubricant, a release agent, or a nucleating agent is contained as the other additive (F), the other additive (F) may be contained in the particles of the polyamide resin composition, or at least a part of the other additive (F) may be attached to the surface of the particles containing the polyamide resin composition.
[0124] As a method for uniformly attaching other additives (F) to the pellet surfaces, a method is preferably a method in which 0.01% to 0.07% of liquid polyethylene glycol is uniformly attached to the pellet surfaces in advance with respect to the total mass of the polyamide resin composition, and then other additives (F) are added and stirred with a stirrer to attach the additives.
[0125] The properties of the other additives (F) are very different, so the appropriate content of each component that does not almost impair the effect of the present embodiment is various. Moreover, those skilled in the art can easily set the appropriate content of each of the other additives. For example, in 100% by mass of the polyamide resin composition, the other additives (F) can be 50% by mass or less, 30% by mass or less, 20% by mass or less, 10% by mass or less, or 5% by mass or less.
[0126] <Method for producing polyamide resin composition>
[0127] The polyamide resin composition of the present embodiment can be produced by mixing a polyamide resin (A), an ethylene-butene copolymer (B), a black colorant (C), a copper compound (D), a fibrous reinforcing material (E) as an optional component, and other additives (F).
[0128] Examples of a method for mixing the components (A) to (D) and, if necessary, the components (E) and (F) include the following methods (1) and (2).
[0129] (1) A method in which the components (A) to (D) are mixed using a Henschel mixer or the like, and the mixture is supplied to a melt kneader for kneading.
[0130] (2) A method in which the components (A) to (D) are mixed in advance using a Henschel mixer or the like using a single-screw or twin-screw extruder to prepare a mixture containing the components (A) to (D), and the mixture is supplied to a melt kneader for kneading.
[0131] The melt kneading temperature is preferably about 1° C. or higher and about 100° C. or lower than the melting point of the polyamide resin (A), and more preferably about 10° C. or higher and about 70° C. or lower than the melting point of the polyamide resin (A).
[0132] As an apparatus for performing melt kneading, any known apparatus may be used, and for example, a single-screw or twin-screw extruder, a Banbury mixer, a melt kneading machine (mixing roll), etc. are preferably used.
[0133] The amount of each component blended when producing the polyamide resin composition of the present embodiment is the same as the content of each component in the above-mentioned polyamide resin composition.
[0134] <Molding>
[0135] The present embodiment is a molded article obtained by molding the polyamide resin composition of the present embodiment described above.
[0136] According to the polyamide resin composition of the present embodiment, various molded products of various parts can be obtained by various conventionally known methods such as injection molding and extrusion molding.
[0137] These various parts can be used, for example, for automobiles, machinery industry, electrical and electronic applications, industrial materials, industrial materials, and daily and household products. In particular, the polyamide resin composition of the present embodiment has excellent impact resistance and heat aging resistance, and does not discolor after aging, so it can be suitably used for applications exposed to a heat environment of 100° C. or above (for example, electric connectors and harness protectors mounted on automobiles, etc.).
[0138] Example
[0139] Hereinafter, the present invention will be described in detail with reference to specific examples and comparative examples, but the present invention is not limited to the following examples.
[0140] Hereinafter, each constituent component of the polyamide resin composition used in the present Example and Comparative Example will be described.
[0141] <Composition>
[0142] [Polyamide resin (A)]
[0143] A-1: Polyamide 66 (PA66) (manufactured by INVISTA, model: TORZEN U3600, melting point 262°C, formic acid relative viscosity (RV) 37.0, amino terminal concentration 55 μmol / g, carboxyl terminal concentration 98 μmol / g)
[0144] The melting point of the polyamide resin (A) is measured in accordance with JIS-K7121 using Diamond DSC manufactured by PERKIN-ELMER.
[0145] The formic acid relative viscosity (RV) of the polyamide resin (A) was measured according to ASTM-D 789. More specifically, the formic acid relative viscosity (RV) was measured at 25° C. using a solution of 8.4% by mass of the polyamide resin dissolved in 90% by mass of formic acid (10% by mass of water).
[0146] The amino terminal concentration of the polyamide resin (A) is measured by neutralization titration as follows.
[0147] First, 3.0 g of the obtained polyamide resin was dissolved in 100 mL of a 90% by mass phenol aqueous solution. Then, the obtained solution was titrated with 0.025 N hydrochloric acid to determine the amino terminal concentration (μmol / g). The endpoint was determined from the indicated value of the pH meter.
[0148] The carboxyl terminal concentration of the polyamide resin (A) is measured by neutralization titration as follows.
[0149] First, 4.0 g of the obtained polyamide resin was dissolved in 50 mL of benzyl alcohol. Then, the obtained solution was titrated with 0.1 N NaOH to determine the carboxyl terminal concentration (μmol / g). The endpoint was determined by the color change of the phenolphthalein indicator.
[0150] [Ethylene-butene copolymer (B)]
[0151] B-1: Maleic anhydride grafted ethylene-butene copolymer (Mitsui Chemicals, Inc., trade name "Tafmer MD715", maleic acid modification rate 0.75%)
[0152] B-2: Maleic anhydride grafted ethylene-butene copolymer (Mitsui Chemicals, Inc., trade name "Tafmer MH5010", maleic acid modification rate 0.5%)
[0153] B-3: Maleic anhydride grafted ethylene-butene copolymer (Mitsui Chemicals, Inc., trade name "Tafmer MH5020", maleic acid modification rate 1.0%)
[0154] B-4: Maleic anhydride grafted ethylene-butene copolymer (Mitsui Chemicals, Inc., trade name "Tafmer MH5040", maleic acid modification rate 2.0%)
[0155] B-5: Ethylene-butene copolymer (Mitsui Chemicals, Inc., trade name "Tafmer DF605", modification rate 0%)
[0156] [Black colorant (C)]
[0157] C-1: Carbon black (Mitsubishi Chemical Corporation, trade name [#980])
[0158] C-2: Aniline black (manufactured by Orient Chemical Industry Co., Ltd., trade name "Nubian Black TN-870")
[0159] [Copper compounds (D)]
[0160] D-1: Cuprous iodide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0161] [Fiber reinforcement material E]
[0162] E-1: Glass fiber (manufactured by Jushi Group Co., Ltd., trade name [ECS10-03-568H-G]
[0163] [Other additives (F)]
[0164] F-1: Dodecanedioic acid (manufactured by Ube Industries, Ltd.)
[0165] <Physical properties and evaluation methods of molded products>
[0166] [Manufacturing of molded products]
[0167] The pellets of the polyamide resin composition obtained in the examples and comparative examples were dried at 80°C for more than 16 hours and less than 24 hours, and the water content in the polyamide resin composition was adjusted to less than 500 mass ppm. Next, an injection molding machine (NEX-50IV, manufactured by Nissei Resin Co., Ltd.) was used to mold the pellets of each polyamide resin composition after adjusting the water content into a multi-purpose test piece (type A, dumbbell-shaped tensile test piece) as a molded product in accordance with ISO3167. It should be noted that the dimensions of the multi-purpose test piece are: total length ≥ 170 mm, distance between handles 109.3 mm ± 3.2 mm, length of parallel portion 80 mm ± 2 mm, radius of shoulder 24 mm ± 1 mm, width of end 20 mm ± 0.2 mm, width of central parallel portion 10 mm ± 0.2 mm, thickness 4 mm ± 0.2 mm. As specific conditions during injection molding, the injection and holding time: 25 seconds, cooling time: 15 seconds, mold temperature: 80°C, barrel temperature: 280°C.
[0168] [Evaluation 1] Impact resistance
[0169] "Charpy impact test"
[0170] Using the multipurpose test piece A, the notched Charpy impact strength was measured in accordance with ISO179.
[0171] [Evaluation 2] Heat aging test
[0172] Using the above-mentioned multi-purpose test piece A, a tensile test was performed at a tensile speed of 5 mm / min in accordance with ISO527, and the initial tensile strength (MPa) (S0) was measured. Next, each multi-purpose test piece (type A) was placed in a Gill oven (manufactured by ESPEC, model: PHH-201, damper opening: 25%) and heated at 150°C for 1000 hours to perform a heat aging test. After 1000 hours, each multi-purpose test piece (type A) was taken out of the oven and cooled at 23°C for 24 hours. Next, each multi-purpose test piece (type A) after the heat aging test was subjected to a tensile test in accordance with ISO527 at a tensile speed of 50 mm / min using the same method as the above method, and the tensile strength (MPa) (S1) after the heat aging test was measured. Next, the tensile strength retention rate (%) was calculated using the formula (1) shown below.
[0173] Tensile strength retention rate (%) = S1 / S0×100 (1)
[0174] From the obtained tensile strength retention rate, the tensile strength retention rate was evaluated according to the following evaluation criteria.
[0175] (Evaluation Criteria)
[0176] 〇 (good): tensile strength retention rate is more than 90%
[0177] △ (poor): tensile strength retention rate is greater than or equal to 70% and less than 90%
[0178] × (bad): tensile strength retention rate is less than 70%
[0179] [Evaluation 3] Discoloration after heat aging
[0180] The color tone of each multi-purpose test piece (type A) was measured using a colorimeter (manufactured by Nippon Denshoku Co., Ltd., ZE6000). Next, the multi-purpose test piece (type A) was placed in a Gir oven (manufactured by ESPEC, model: PHH-201, damper opening: 25%) and heated at 150°C for 1000 hours to conduct a heat aging test. After 1000 hours, each multi-purpose test piece (type A) was taken out of the oven, cooled at 23°C for 24 hours, and then the color tone was measured using the same method as above. Based on the L value, a value, and b value obtained by the measurement before and after heat aging, the color tone change caused by heat aging was obtained, and ΔL*, Δa*, and Δb* were calculated. These values were substituted into the following formula (2) to calculate the color difference ΔE representing the color tone change before and after heat aging.
[0181] ΔE=[(ΔL*) 2 +(Δa*) 2 +(Δb*) 2 ] 1 / 2 (2)
[0182] The obtained ΔE was used to judge the discoloration property due to heat aging according to the following evaluation criteria.
[0183] (Evaluation Criteria)
[0184] ○ (Excellent): Color difference ΔE less than 8.0
[0185] △ (good): color difference ΔE is greater than or equal to 8.0 and less than 12.0
[0186] × (bad): color difference ΔE is 12.0 or more
[0187] <Production of Polyamide Resin Composition>
[0188] [Example 1]
[0189] (Production of polyamide resin composition)
[0190] A TEM35 mm twin-screw extruder manufactured by Toshiba Machine Co., Ltd. (set temperature: 280°C, screw speed 300 rpm) was used to supply a mixture obtained by blending a polyamide resin (A), an ethylene-butene copolymer (B), a black colorant (C), and a copper compound (D) in advance from a top feed port set at the uppermost upstream portion of the extruder. The molten kneaded product extruded from the die was cooled in a strand form and pelletized to obtain a polyamide resin composition PA-a1. The mass ratios of the components are shown in Table 1.
[0191] [Examples 2 to 9, 12 to 13, Comparative Examples 1 to 11]
[0192] Except having changed each structural component into the structure described in Table 1, it carried out similarly to Example 1, and obtained the polyamide resin composition.
[0193] [Example 10]
[0194] (Production of polyamide resin composition)
[0195] A TEM35mm twin-screw extruder manufactured by Toshiba Machine Co., Ltd. (set temperature: 280°C, screw speed 300rpm) was used to supply a mixture obtained by pre-blending polyamide resin (A), ethylene-butene copolymer (B), black colorant (C), and copper compound (D) from the top feed port set at the upstream end of the extruder. Glass fiber (E-1) was supplied from the side feed port set at the downstream end of the extruder. The molten kneaded product extruded from the die was cooled in the form of strands and granulated to obtain a polyamide resin composition PA-a10. The mass ratio of each component is shown in Table 1.
[0196] [Example 11]
[0197] (Production of polyamide resin composition)
[0198] A TEM35 mm twin-screw extruder manufactured by Toshiba Machine Co., Ltd. (set temperature: 280°C, screw speed 300 rpm) was used to supply a mixture obtained by blending polyamide resin (A), ethylene-butene copolymer (B), black colorant (C), copper compound (D), and other additives (F-1) in advance from the top feed port set at the most upstream part of the extruder. The molten kneaded product extruded from the die was cooled in the form of strands and granulated to obtain a polyamide resin composition PA-a11. The mass ratios of the components are shown in Table 1.
[0199] Various physical property measurements and evaluations were performed by the above methods. The evaluation results are shown in Table 1 below.
[0200] [Table 1]
[0201]
[0202] As shown in the above results, it was confirmed that the polyamide resin composition according to the present embodiment has both impact resistance and heat aging resistance, and is excellent in color stability after heat aging even when colored with a black colorant.
Claims
1. A polyamide resin composition, wherein The polyamide resin composition comprises, relative to 100 parts by mass of the polyamide resin (A): 1.0 to 30.0 parts by mass of an ethylene-butene copolymer (B), 0.01 to 1.0 parts by mass of a black colorant (C), and Copper compounds (D), The ethylene-butene copolymer (B) includes a functional group reactive with the polyamide resin (A), and the mass ratio of the functional group is 0.6 mass % or more and 3.5 mass % or less relative to 100 mass % of the ethylene-butene copolymer. The mass ratio of the copper compound (D) is 0.001 to 0.5 parts by mass in terms of copper element content relative to 100 parts by mass of the polyamide resin (A).
2. The polyamide resin composition according to claim 1, wherein The ethylene-butene copolymer (B) is a maleic anhydride grafted ethylene-butene copolymer.
3. The polyamide resin composition according to claim 1, wherein The black colorant (C) is at least one selected from the group consisting of carbon black and aniline black compounds.
4. The polyamide resin composition according to claim 1, wherein The polyamide resin (A) is at least one selected from the group consisting of polyamide 66, polyamide 66 / 6I, polyamide 610, polyamide 612, polyamide 6I, and polyamide 6.
5. A molded article, wherein The molded article is a molded article of the polyamide resin composition according to any one of claims 1 to 4, and the molded article is used for exposure to a heat environment of 100° C. or higher.
6. The molded article according to claim 5, wherein The molded product is a strapping belt or a protector for an automobile.
